Educação física: os motivos dessa escolha profissional - Coutinho, Miguel Posso (2005)
The choice of profession is one of the greatest challenges we confront in life due to the importance it represents and the difficulties that we face. As well as this, we are not always prepared to make this choice. A good choice of profession is valuable to the individual as well as to the community of which he is part, for it isthrough the profession we perform a social function.